Socio-Emotional Competencies Required by School Counsellors to Manage Disruptive Behaviours in Secondary Schools - Ángela Serrano; Roberto Sanz; Juan Luis Cabanillas; Elena López-Lujan (Children, 2023)
This article identifies the socio-emotional competencies of school counsellors working with children and adolescents. The aim is to address problems related to mental health and conflict and to implement training programmes. The study sample was composed of 149 counsellors working in schools. The instruments used were the CCPES-II (questionnaire on teacher competences) and a series of open-ended questions on conflict resolution. A mixed methodology was used, with a concurrent triangulation design with two phases: a quantitative one (QUAN) and a qualitative one (QUAL). Univariate, bivariate, and correlation quantitative analyses were performed. Parametric and non-parametric tests were applied depending on the number of dependent and independent variables. The qualitative analysis was performed with the NVivo 12 computer programme, which determines word frequencies using a classic content analysis. The results confirm the relationship between socio-emotional training and rapid response to school conflict; the generalised view that conflicts are difficult to anticipate and, thus, to prevent; and the demand for specific training in socio-emotional competences, intervention strategies, more specialised school staff, more time for intervention with and support for families, and more socio-professional recognition.